Stress and Conflict in Educational Institutions - Ellen Okta Divy; Nyayu Khodijah; Febriyanti Febriyanti (Sustainable, 2023)
Stress and conflict cannot be separated because severe and prolonged Stress will occur, causing conflicts within and between individuals in the organization. Conflicts can occur in the relationship between the leader (manager) and subordinates due to the hierarchical nature of the relationship. Conflict at lower levels can be considered part of management that is expected to change significantly. But, emotions play a significant role if the conflict is severe and profound. It shows the weakness of the organization and is placed at a disadvantage. In this context, the organization's leader figure (manager) is vital in handling conflicts. The purpose of this article is to examine Stress and conflict in organizations.